Implementation of the WMA Method in the Stock Forecasting System of Eva Fashion Stores - Gabriel Ardi Hutagalung (Politeknik Negeri Medan, 2021)
Eva Fashion Clothing Store is a business selling goods that only sells various kinds of clothing products. In this shop, it is often difficult to predict future product inventory based on previously recorded data. So we need a system that can predict sales to prepare clothing stocks in the future. In developing this forecasting system, the author will use the Weighted Moving Average forecasting method. Forecasting using the weighted moving average method can predict how much stock of goods must be purchased for the next period. Forecasting calculations for the coming period are based on the calculation of the previous quarterly data and can also be done based on the selection of the desired period. The purpose of this research is to analyze forecasting inventory for sales of products or goods in the next period and to build a system in predicting future sales value to increase store business